IR-assisted ionization of helium by attosecond extreme ultraviolet radiation - Ranitovic, P.; Tong, X. M.; Gramkow, B.; De, S.; DePaola, B.; Singh, K. P.; Cao, W.; Magrakvelidze, M.; Ray, D.; Bocharova, I.; Mashiko, H.; Sandhu, A.; et al. (My University, 2010)
Attosecond science has opened up the possibility of manipulating electrons on their fundamental timescales. Here, we use both theory and experiment to investigate ionization dynamics in helium on the attosecond timescale by simultaneously irradiating the atom with a soft x-ray attosecond pulse train (APT) and an ultrafast laser pulse. Because the APT has resolution in both energy and time, we observe processes that could not be observed without resolution in both domains simultaneously. We show that resonant absorption is important in the excitation of helium and that small changes in energies of harmonics that comprise the APT can result in large changes in the ionization process. With the help of theory, ionization pathways for the infrared-assisted excitation and ionization of helium by extreme ultraviolet (XUV) attosecond pulses have been identified and simple model interpretations have been developed that should be of general applicability to more complex systems (Zewail A 2000 J. Phys. Chem. A 104 5660–94).